Kilconnell Franciscan Friary, south nave wall, tomb niche, jamb and arch - O'Donovan, Danielle (My University, 2009)
Jamb and arch moulding of tomb niche. Moulding, from intrados, comprises: hollow chamfer, right-angled rebate, hollow chamfer, right-angled rebate, hollow chamfer. The elements grow larger as the moulding progresses from the inner to the outer face. This, though a simple design feature, is unusual in Irish mouldings and is seen rarely. A similar graduation in size can be found in the jamb of the tomb niche in the north chancel wall at St. Mary Youghal.
Tomb niche
Keywords: Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Franciscan; Funerary monuments; Late Medieval; moldings, hollow